1049. Breakthrough SARS-CoV-2 Infections after Vaccination in the North Carolina COVID-19 Community Research Partnership (NC-CCRP). (15th December 2022) - Uschner, Diane; Bott, Matthew; Strylewicz, Gregory B; Edelstein, Sharon; Miller, Kristen; Lagarde, William H; Keating, Joseph; Schieffelin, John; Weintraub, William; Yukich, Joshua; Ahmed, Amina; Berry, Andrea A; et al.
Abstract: Background: We characterize the incidence and risk factors of SARS-CoV-2 breakthrough infections in the NC-CCRP. Cumulative Incidence of Breakthrough infections after Self-reported Symptomatic SARS-CoV-2 Test Cumulative incidence curves (1 minus the unadjusted Kaplan–Meier risk), number at risk at each time point for the first self-reported symptomatic positive SARS-CoV-2 test, starting from full vaccination among participants who reported full vaccination. Methods: The NC-CCRP is an observational cohort study assessing COVID-19 symptoms, test results, vaccination status, and risk behavior via daily email or text surveys. Cox models were used to estimate hazard rates. Fixed covariates were age at enrollment, race/ethnicity, sex, county of residence classification, vaccine product, and healthcare worker status. Time varying covariates were vaccination rate in county of residence, mask usage in the week prior, the Delta time frame, the Omicron time frame, and receipt of a vaccine booster. Results: Among 15, 808 eligible adult participants, 638 (4.0%) reported a positive SARS-CoV-2 test after vaccination from 01/15/2021 to 01/03/2022. The breakthrough rate increased with time from vaccination (Figure), with a cumulative incidence of 6.95% over 45 weeks of follow-up. Factors associated with a lower risk of breakthrough infection (p< 0.05) included older age (HR 0.7 for participants 45-64 years and 0.41 for those > 65 years compared to those 18-44 years), prior SARS-CoV-2 infection (HR 0.58), higher rates of mask use (HR 0.66), and receipt of a booster vaccination (HR 0.33). Higher rates of breakthrough infection were reported by participants vaccinated with BNT162b2 (HR 1.35) or Ad26.COV2.S (1.74) compared to mRNA-1273, those residing in suburban (HR 1.33) or rural (1.24) counties compared to urban counties, and during circulation of the Delta (3.54) and Omicron (16.68) variants compared to earlier time periods. There was no association of breakthrough infection with sex, race/ethnicity, healthcare worker status, or vaccination rate in the county of residence. Conclusion: In this real-world analysis, risk of breakthrough infections increased with time since vaccination, with some variability among the specific vaccine products. Risk increased dramatically during the Omicron surge. Higher rates among younger individuals may reflect more frequent, or higher risk exposures, including those related to childcare. Significantly lower rates of breakthrough associated with mask wearing and receipt of a booster highlight specific measures that individuals can take to minimize the risk for COVID-19. Disclosures: Michael S. Runyon, MD, MPH, Abbott Laboratories: Grant/Research Support|Roche Diagnostics Operations, Inc: Grant/Research Support.